Calving Bay dynamics and ice sheet retreat up the St. Lawrence Valley system - Thomas, R. (Géographie physique et Quaternaire)

(untitled) (Les Presses de l’Université de Montréal, 1977)
Ice streams that drain marine ice sheets are particularly susceptible to catastrophic retreat because they flow through bedrock troughs, and grounding line migration would produce a calving bay filled either with an ice shelf or with icebergs. Geological evidence suggests that a calving bay formed in the Laurentian Channel and the St. Lawrence valley after the late-Wisconsin maximum. Retreat rates in this calving bay are calculated for a variety of possible models assuming that locally the late-Wisconsin Laurentide ice sheet extended to the edge of the continental shelf. If an ice shelf forms in front of the retreating grounding line, and the shear stress between the ice shelf and its margins is one bar, retreat continues for only 150 km. Further retreat requires lubrication by ice with a strain-dependent preferred crystal fabric that develops between the ice shelf and its sides, or by complete removal of the ice shelf. Under these conditions the first 300 km of retreat takes at least 3000 to 6000 years. Thereafter, further retreat is rapid until, if a lubricated ice shelf is present, a new equilibrium grounding line is established about 1100 km from the edge of the continental shelf. If massive calving of icebergs occurred at, or near the grounding line, then retreat would continue up the St. Lawrence valley through to Lake Ontario. Of the various models considered, the minimum time taken for retreat from a point 300 km inland from the edge of the continental shelf through to Lake Ontario is about 2000 years.